Concept for improving customs and tariff mechanisms for regulating international trade - T. M. Vorotyntseva (Управление)
The purpose of the study is to develop main provisions of the concept of improving customs tariff mechanisms for regulating international trade.   As the subject of the study, the fundamental elements of the customs mechanisms development concept have been defined: principles, tasks, tools, etc.   In order to develop competitiveness in the world economy and international trade, it is relevant to adapt to the changing conditions of international business and identify the area where it is necessary to take measures to support it. The necessity of improving customs mechanisms for regulating international trade has been substantiated. The research methodology is based on the scientific literature analysis, comparative analysis, statistical data systematization and analysis. The main study result is the presentation of the concept of the processes of improving customs-tariff mechanisms of international trade and its elements regulation, aimed at increasing the effectiveness of customs-tariff measures for developing international trade in the Eurasian Economic Union member states. The concept proposes directions for systematization and improvement of supranational level customs regulation tools, which remains an important task for the near future, especially in view of changes in the foreign trade of Russian enterprises as a result of the trade conflicts aggravation caused by political and economic relations deterioration between the US, the European Union member states, and Russia. The study results application scope can be determined by a wide range of users, such as government executive authorities and customs service, logistics and commercial companies, as well as the scientific community. In the future, the proposed concept application in practical activities will ensure a business-friendly environment creation in accordance with the requirements of the general trade and customs policy and investments promotion related to the international trade development.